Daily life habits associated with eveningness lead to a higher prevalence of dental caries in children - Shinya Nishide; Toshihiro Yoshihara; Hirohisa Hongou; Takashi Kanehira; Yasutaka Yawaka (Elsevier, 2019)
Background/purpose: Circadian rhythm is an endogenous daily variation observed in most physiological functions including salivary secretion. Irregular lifestyle causes many diseases such as obesity and sleep disorders. The aim of this study is to examine the effects of the timings of sleep and meal on the prevalence of dental caries. Materials and methods: Study was conducted at university hospital in Japan. We asked 230 children (1-16 years old) to record the following life habits for 8 days: waking time, bedtime, mealtimes, snacking frequency, and tooth brushing frequency. We analyzed sleep habits from all data and compared dental caries and life habits using data from subjects with primary (2-7 years old) or permanent (11-16 years old) dentition period. Results: The number of dental caries assessed using the decay or filled teeth (dft) index correlated with bedtime, supper time, regularity of supper time, and snacking frequency in subjects with primary dentition. Multiple regression analysis revealed that bedtime and snacking frequency were mutually independent risk factors for dental caries. No correlations were found between the prevalence of dental caries and other measurement items. The number of caries correlated with the regularity of supper time and age in subjects with permanent dentition. Conclusion: Children with daily life habits associated with eveningness have a higher prevalence of dental caries. Keywords: Dental caries, Oral health, Circadian rhythms, Life habits, Questionnaire